THE RELATIONSHIP BETWEEN LANGUAGE AND THOUGHT: THE SAPIR-WHORF HYPOTHESIS - Manzuraxon Xolmirzayeva (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article provides a detailed analysis of the relationship between language and thought based on the Sapir-Whorf hypothesis. It explores how language influences perception, cognition, and worldview. The concepts of linguistic determinism and linguistic relativity are discussed with examples.